Do high school friends still matter for health behavior in adulthood? Variations in smoking trajectories by adolescent peer smoking networks, race/ethnicity, and gender - Kaitlin Shartle (SSM: Population Health, 2021)
Peers play an influential role in the initiation of smoking during adolescence. However, there has been limited literature examining whether adolescent peers are associated with longer-term patterns of smoking. This study uses data from the National Longitudinal Study of Adolescent to Adult Health to examine whether age-based trajectories of smoking likelihood from adolescence to adulthood are associated with the number of adolescent friends who smoked and how this association differs by race/ethnicity and gender. Findings using multilevel growth curve models indicate that individuals who have more adolescent friends who smoked have higher probabilities of smoking during adolescence than those with no adolescent smoking friends. As individuals age into adulthood, the association between adolescent friends’ smoking behavior and individual-level smoking begin to dissipate but does not completely disappear. Further analyses show that there are no differences in this association by gender, but there are differences by race/ethnicity. These findings suggest that high school friends continue to be associated with trajectories of smoking even twenty years after high school. These results indicate that anti-smoking campaigns should take a network approach to preventing smoking in adolescence as well as recognize that the same campaign strategy may not work for all groups.